Highly biocompatible zwitterionic dendrimer-encapsulated platinum nanoparticles for sensitive detection of glucose in complex medium. (24th May 2019) - Cui, Yanshuai; Zhang, Jin; Yu, Qingyu; Guo, Xiaolei; Chen, Shengfu; Sun, Haotian; Liu, Sihang; Wang, Longgang; Lai, Xiang; Gao, Dawei
Abstract : The sensitive detection of glucose using zwitterionic dendrimer-encapsulated platinum nanoparticles was not affected by proteins. Abstract : The development of ultra-small platinum nanoparticles is very important for the sensitive detection of glucose in complex medium without protein interference. Zwitterionic dendrimer-encapsulated platinum nanoparticles (Pt n -G5MC NPs) have been developed and studied for the highly sensitive and selective colorimetric detection of glucose. Firstly, zwitterionic dendrimer (G5MC) was obtained by surface modification of generation 5 poly(amidoamine) dendrimer with maleic anhydride and cysteamine. The calculated average diameters of Pt nanoparticles (Pt NPs) for Pt n -G5MC ( n = 55, 110, and 165) were 1.64 ± 0.22, 2.09 ± 0.24, and 2.98 ± 0.29 nm, respectively. Pt n -G5MC NPs not only had high stability in various pH solutions and fibrinogen solutions, but also showed no noticeable cytotoxicity against HUVEC cells and HeLa cells. In addition, Pt n -G5MC NPs catalyzed oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) with H2 O2 to generate blue oxidized TMB (oxTMB), indicating their peroxidase-like property. This peroxidase-like reaction followed a typical Michaelis–Menten kinetics. Furthermore, this colorimetric reaction was used for glucose detection with high sensitivity and selectivity. The linear range of glucose concentration with absorbance at 652 nm was from 7 to 1380 μM, and the detection limit was 2.8 μM. More importantly, the relative activity of Pt n -G5MC NPs was not affected by proteins. These enhanced properties are attributed to the ultra-small size of Pt NPs and high stability of Pt55 -G5MC NPs in complex medium. The glucose concentration in saliva as a real sample was found to be 0.18 mM. The proposed glucose sensor could have promising applications for glucose detection in biocatalysis and bioassays in the future.